The Role of Spirituality for Coping with Cancer and the Spiritual Care Needs of Women with Breast Cancer and their Family Caregivers in Turkey: A Qualitative Study - Keten Edis, Elif (Journal of religion and health, 2024)
This study aims at determining the spiritual care needs of women with breast cancer and their family caregivers, as well as the effect of spirituality on coping with this illness. This qualitative research utilized a phenomenological design. In-depth individual interviews were conducted with breast cancer women and family caregivers. A total of 26 participants (13 women with breast cancer and 13 family caregivers) were involved. The data were examined using inductive thematic analysis. Three main themes were identified: "Being diagnosed with breast cancer; its emotional and life-related impacts;" "Spirituality in fighting with cancer;" and "Caring period and needs". The results showed that the diagnosis and treatment of breast cancer have multifaceted effects on women and their family caregivers. Spirituality was found to be an essential factor in coping with cancer for women with cancer and their family caregivers. In addition, the results showed that women and family caregivers have some unmet spiritual care needs.